Putting interoperability to the test: building a large reusable assessment item bank - Niall Sclater; Mary MacDonald (Association for Learning Technology, 2004)
The COLA project has been developing a large bank of assessment items for units across the Scottish further education curriculum since May 2003. These will be made available to learners mainly via colleges' virtual learning environments (VLEs). Many people have been involved in the development of the COLA assessment item bank to ensure a high level of technical and pedagogical quality. Processes have included deciding on appropriate item types and subject areas, training authors, peer-reviewing and quality assuring the items and assessments, and ensuring they are tagged with appropriate metadata. One of the biggest challenges has been to ensure that the assessments are deliverable across the four main virtual learning environments in use in Scottish colleges–and also through a stand-alone assessment system. COLA is significant because no other large project appears to have successfully developed standards-compliant assessment content for delivery across multiple VLEs. This paper discusses how COLA has dealt with the organizational, pedagogical and technical issues which arise when commissioning items from many authors for delivery across an educational sector.